O Odkształceniach i Naprężeniach Termicznych w Cienkich Płytach Prostokątnych i Kołowych o Zmiennej Grubości - Thrun, Z. (Engineering Transactions, 1956)
Differential equations of deflection are derived in Cartesian and polar coordinates for plates of arbitrarily variable thickness, subjected to temperature arbitrarily distributed oved both faces of the plates and linearly variable over the thickness. Rectangular plates of linearly variable thickness clamped or simply supported on two edges are also investigated. Solution in the case of thickness constituting a quadratic function is obtained for circular plates.The results obtained for a numerical example are compared with the corresponding results for a plate of constant mean thickness, subjected to a constant temperature difference. Finally, a solution for a circularplate of axially symmetrical rigidity and temperature distribution is obtained by means of the method of finite differences.